The process of lithuanian mathematical terminology in 1920–1940 - Pekarskas, Vidmantas; Pekarskienė, Aldona (Lietuvos matematikos rinkinys, 2001)
Lithuanian mathematical terms used in mathematical textbooks for the secondary schools issued in 1920–1940 are compared in the article.